Human Capital, Gender & Economic Growth of India: An Auto-Regressive Distributed Lag Approach: Examining the Role of Education and Gender in India's Economic Growth (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Human Capital is an essential prerequisite of sustainable economic growth. The investment in education allows for improvements in the technical capabilities related to exploring of new ideas and innovations which enables the improvement in the quality of human capital of the country. It enhances the quality of life and leads to collective benefits to individuals and societies. The paper examines the short and long run relationship between defined by education variables and economic growth for India using Autoregressive Distributed Lag (ARDL) method of bound testing approach to co integration and error correction model using the annual data for the period 1970 – 2018. The study has incorporated Gross enrolment ratio at primary, secondary and tertiary level education as a proxy for human capital. The educational variables are also analyzed by gender to see impact of female education on economic growth. The study found the existence of co integration between all educational variables and economic performance of the country. The primary education level is found to be growth inducing factors in the short- run and long run. The tertiary level education is found to have positive and significant contribution to the economic growth in the long run. The gender analysis shows that primary male education level has a higher contribution to the growth in the short as well as long run. The female tertiary education level has the higher contribution to the economic growth of the country in the long run as compared to the males. Though, equal opportunity to education should be provided to male and female yet special attention need to be given to improve the enrolment rates of female in the higher education. The study also provides evidence that the secondary level educated persons generally with low professional and technical skills are unable to contribute to the economic activity of the country. The education system needs to be revamped to focus on skill based professional education at the secondary level with gender neutral policy framework.